1996
DOI: 10.1148/radiology.199.2.8668817
|View full text |Cite
|
Sign up to set email alerts
|

Drainage catheters: in vitro comparison of internal retention mechanisms.

Abstract: In five drainage catheters, internal retention mechanisms (locking pigtail [14 and 8 F], inflatable balloon [14 F], or wings [14 and 24 F]) were evaluated for resistance to and distortion from dislodgment. Catheters were inserted into simulated tissue, and weight was added until dislodgment occurred. Resistance to dislodgment increased when the mechanisms were locked; the locking pigtail supported the most weight. Distortion caused by dislodgment was minimal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In our search, only one paper was found to have adequate information regarding these three different types of internal retention mechanisms. This in vitro study evaluated the resistance to dislodgment of the three different retention mechanisms discussed and found that the balloon and suture locking mechanisms were the most effective (Figure 7 ) [ 14 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In our search, only one paper was found to have adequate information regarding these three different types of internal retention mechanisms. This in vitro study evaluated the resistance to dislodgment of the three different retention mechanisms discussed and found that the balloon and suture locking mechanisms were the most effective (Figure 7 ) [ 14 ].…”
Section: Reviewmentioning
confidence: 99%
“… Bar graph indicating that the Foley and pigtail catheters performed the best when tested for resistance to dislodgment [ 14 ] …”
Section: Reviewmentioning
confidence: 99%